Job Satisfaction as a Mediating Variable of Work Professionalism, Organizational Commitment, and Employee Performance in the Animal Feed Industry - Handayani, Maidiana Astuti; Anggarini, Defia Riski; Marini, Dewi (The Indonesian Institute of Science and Technology Research, 2025)
This study investigates the influence of work professionalism and organizational commitment on employee performance, with job satisfaction as a moderating variable, at PT. Japfa Comfeed Indonesia Tbk, Bandar Lampung Branch. Using a quantitative approach, data were collected through questionnaires distributed to 116 employees, selected from a population of 163 using the Slovin formula. The analysis used Partial Least Squares (PLS) through the SEM-PLS approach with WarpPLS 7.0 software. The findings reveal that both work professionalism and organizational commitment positively affect employee performance, with path coefficients of 0.365 (p < 0.001) and 0.321 (p < 0.001), respectively. However, job satisfaction does not significantly moderate the relationship between work professionalism and performance (β = -0.003, p = 0.448) or organizational commitment and performance (β = 0.106, p = 0.122). These results suggest that while professionalism and commitment are key drivers of performance, job satisfaction does not significantly mediate these relationships within this organizational context.